"Takotsubo effect" in patients with ST segment elevation myocardial infarction. Issue 7 (October 2020) - Lei, Juan; Chen, Jian; Dogra, Megha; Gebska, Milena A; Shetty, Suchith; Ponnapureddy, Rakesh; Roy, Shubha D; Wang, Jingfeng; Liu, Kan
Background: Myocardial infarction can be a trigger of Takotsubo syndrome. We recently characterized imaging features of acute myocardial infarction-induced Takotsubo syndrome ("Takotsubo effect"). In this study, we investigate diagnostic and prognostic implications of Takotsubo effect in patients with anterior wall ST-segment elevation myocardial infarction. Methods: We enrolled 111 consecutive patients who developed anterior wall ST-segment elevation myocardial infarction and received percutaneous coronary intervention, and studied systolic/diastolic function, hemodynamic consequences, adverse cardiac events, as well as 30-day and five-year outcomes in patients with and without Takotsubo effect. Results: Patients with Takotsubo effect showed significantly worse average peak systolic longitudinal strain (–9.5 ± 2.6% vs –11.1 ± 3.6%, p  = 0.038), left ventricular ejection fraction (38.5 ± 6.8% vs 47.7 ± 8.7%, p  = 0.000) and myocardial performance index (0.54 ± 0.17 vs 0.37 ± 0.15, p  = 0.000) within 48 h of myocardial infarction. There was no significant difference between the two groups in diastolic ventricular filling pressures, hemodynamic consequences, and 30-day rehospitalization and mortality (Gehan-Breslow-Wilcoxon test: p =  0.157). However, patients with Takotsubo effect developed more major adverse cardiac events (log-rank test: p =  0.019) when tested at the five-year follow-up. Cox regression analysis revealed that age, hypotension, tricuspid annular plane systolic excursion, and Takotsubo effect were independent prediction factors for five-year major adverse cardiac events. The Doppler/tissue Doppler parameter E/e' correlated with MACE only in patients without Takotsubo effect. Conclusion: Takotsubo effect secondary to anterior ST-segment elevation myocardial infarction predicts a worse long-term prognosis.